PENILAIAN BAHAN AJAR MODUL MATERI “PENERAPAN DESAIN BUSANA UNTUK BERBAGAI BENTUK TUBUH WANITA” - Syela, Yosia; Melly Prabawati (Practice of Fashion and Textile Education Journal, 2022)
This study aims was to created and to know Assestment of “”design implementation for various female body shape module”. The method used in this research was a pre-experimental design with one-shut case study and used quantitative descriptive to collected the data. The research used a single variable, design implementation for various female body shape module. The indicators of this research is aspects of material, aspects of presentation and aspects of language, self instruction, self contained, stand alone, adaptive, and user friendly, used a questionnaire instrument closed-open with panelists to supported a data as of the collected technique. The results of the research showed that the assessment of design implementation for various female body shape module based on the evaluation of the material and media experts is in the Very Good category with the percentage is 87,5%. The percentage of material propelness is 85% with the highest poin is the material aspect with the percentage is 87.5% and media propelness is 90% with the highest poin is Self Instructional aspects is 92.5%. The module is in the category very good because design implementation for various female body shape matched the criteria based on material experts and media experts. Self Instructional Aspects is the highest aspect that affects the results of the assessment of this study.